We have the following:
We must find the equation in each case, first calculating the slope and then the intercept with y, and finally we go to the standard form
The slope is:
[tex]m=\frac{y_2-y_1}{x_2-x_1}[/tex]1. (-1,5), (0,3), (3,9)
[tex]m=\frac{9-5}{3-(-1)}=\frac{4}{3+1}=\frac{4}{4}=1[/tex]now, for intercept with y:
x = 0, y = 3
m = 1
[tex]\begin{gathered} y=mx+b \\ 3=1\cdot0+b \\ b=3 \end{gathered}[/tex]The standard form:
[tex]\begin{gathered} y=x+3 \\ y-x=3 \end{gathered}[/tex]2. (1,2), (3,4), (6,-8)
[tex]m=\frac{-8-2}{6-1}=\frac{-10}{5}=-2[/tex]now, for intercept with y:
x = 3, y =4
m = -2
[tex]\begin{gathered} y=mx+b \\ 4=-2\cdot3+b \\ b=4+6 \\ b=10 \end{gathered}[/tex]The standard form:
[tex]\begin{gathered} y=-2x+10 \\ y+2x=10 \end{gathered}[/tex]